2002
DOI: 10.1055/s-0038-1632736
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete ossification of the humeral condyle as the cause of lameness in dogs

Abstract: SummaryIn a retrospective and prospective trial over six years, 17 joints from 13 dogs presented with incomplete ossification of the humeral condyle (IOHC) were included. All dogs showed lameness of the forelimb but no humeral condylar fractures. One dog showed a fracture of the olecranon. Four of the bilaterally affected dogs showed only unilateral lameness. 53.8% of the dogs (7/13) were younger than one year. With regard to breed distribution, the German Wachtel was most frequently represented with three dog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 6 publications
0
14
1
Order By: Relevance
“…34 The prevalence of HIF in dogs in the United Kingdom is unknown 15 but likely relatively low, as reflected in the sample sizes of this study and that of previous studies. 6,14,16,18,19 A downward trend in complication rate is expected as surgeons become more proficient with the procedure. Indeed, other authors 14 recently reported a complication rate of 24.9%, although this was not their primary objective.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…34 The prevalence of HIF in dogs in the United Kingdom is unknown 15 but likely relatively low, as reflected in the sample sizes of this study and that of previous studies. 6,14,16,18,19 A downward trend in complication rate is expected as surgeons become more proficient with the procedure. Indeed, other authors 14 recently reported a complication rate of 24.9%, although this was not their primary objective.…”
Section: Discussionmentioning
confidence: 99%
“…A medial or lateral approach to the humeral condyle is made, and a variably sized screw 13 is placed in position or lag fashion. 14,15 Complementary use of fluoroscopy, arthroscopy, three-dimensional (3D)-printed drill guides or cannulated drill systems has been described [16][17][18][19] and an autograft or allograft may be placed at the fissure site. 20,21 Various HIFspecific implant systems have been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Surgical site infection (SSI) is the most commonly reported complication following humeral intracondylar fissure surgical management. [1][2][3][4][5][6] Despite the high prevalence of SSI following humeral intracondylar fissure surgery, a notable variability between studies has been observed, with some authors documenting no postoperative SSI [7][8][9] and others recording SSI rates ranging between 5 and 42%. [1][2][3][4][5][6]10,11 In some of these studies, the incidence of SSI considerably exceeds the average reported SSI rates associated with other commonly performed clean, elective orthopaedic surgeries in the dog (1.3-11%).…”
Section: Introductionmentioning
confidence: 99%
“…Humeral intracondylar fissure (HIF) is an uncommonly reported cause of thoracic limb lameness in dogs. [1][2][3] English Springer Spaniels are reported to have a high incidence of HIF, which has been observed in 14% of English Springer Spaniels with no recent history of lameness. 4 In one study, 18% of elbows with HIF managed nonsurgically progressed to fracture and 24% required surgery.…”
Section: Introductionmentioning
confidence: 99%